Pengaruh Permainan Edukatif terhadap Interaksi Sosial Siswa Taman Kanak-kanak - Indrawan, Putu Agus; Mando, Betrics Maria; Suriata, Suriata (Jurnal Kajian Bimbingan dan Konseling, 2017)
The aims of this study is to determine the effect of educational game on kindergarten students’s social interaction. This quantitative research uses Quasi Experimental research design in Reversal Time Series Design. The population in this study were 56 B1 grade kindergarten students of Taman Kanak-kanak St. Francis Xaverius Tarakan, then we took 10 of them as a sample. The data collection technique used is using observation. The data were analysed using graphical analysis technique, then a decision were made based on: frequency, latency, tendency of stability, tendency of chart direction, and level change. The results show that educational games have a significant positive effect on kindergarten students’s social interaction.